Experimental yellow fever virus infection in the golden hamster (Mesocricetus auratus). I. Virologic, biochemical, and immunologic studies - Tesh, Robert B (2001)
This report describes the clinical laboratory findings in golden hamsters experimentally infected with yellow fever (YF) virus. An accompanying paper describes the pathologic findings. Following intraperitoneal inoculation of a virulent strain of YF virus, hamsters developed a high-titered viremia (up to 109/mL) lasting 5–6 days and abnormal liver function tests. YF hemagglutination–inhibiting antibodies appeared 4 or 5 days after infection, often while viremia was still present. The mortality rate in YF-infected hamsters was variable, depending on the virus strain and the age of the animals. Clinical and pathologic changes in the infected hamsters were very similar to those described in experimentally infected macaques and in fatal human cases of YF, which indicates that the golden hamster may be an excellent alternative animal model, in place of nonhuman primates, for research on the pathogenesis and treatment of YF and other viscerotropic flavivirus diseases.